5(c-1)+2=3(c+1)-2

Simple and best practice solution for 5(c-1)+2=3(c+1)-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(c-1)+2=3(c+1)-2 equation:



5(c-1)+2=3(c+1)-2
We move all terms to the left:
5(c-1)+2-(3(c+1)-2)=0
We multiply parentheses
5c-(3(c+1)-2)-5+2=0
We calculate terms in parentheses: -(3(c+1)-2), so:
3(c+1)-2
We multiply parentheses
3c+3-2
We add all the numbers together, and all the variables
3c+1
Back to the equation:
-(3c+1)
We add all the numbers together, and all the variables
5c-(3c+1)-3=0
We get rid of parentheses
5c-3c-1-3=0
We add all the numbers together, and all the variables
2c-4=0
We move all terms containing c to the left, all other terms to the right
2c=4
c=4/2
c=2

See similar equations:

| –9+8v=9v | | 2(2x+1)=6x-20 | | 8a=123 | | -2(x-10)=30 | | 1-q=-3-2q | | 6m+5=5 | | 2z+4/3=4 | | 77=11g | | 3/4x-7+2=(x-2) | | 2x1/4x=9 | | 3(x+4)=5(x-6)+36 | | 5(k-4)+k=-8 | | x+39=90+147=360 | | 120+22x+4=15+5 | | -10-1-9w=7-6w | | r/14=3 | | 532=4z | | 4x+25=39 | | 5y/100=y-11970 | | 5(c-1)+2=3(c=+1)-2 | | 4x+10=39 | | (1/3^x)=81^-1 | | 10y–2y=64* | | 165x=-1580 | | 18x+3/4=336 | | 4h-11=45 | | 17=p | | 7x+12+2=44 | | 5(c-1)+2=3(c-1)-2 | | x/3-9=-8 | | 4y-36=2y=42 | | F(4)=-1/2x+2 |

Equations solver categories